Participação do Agente Indígena de Saúde no Acompanhamento Pré-Natal da Mulher Guarani e Kaiowa - ELLEN CAROLINE RODRIGUES BARRETOS (2021)
Indigenous Health Agents (AIS) are mediators between the multidisciplinary indigenous health team (EMSI) and indigenous women, and their work contributes to compliance with the guidelines proposed in the National Policy for Indigenous Health Care. They are located in the same territory as the indigenous pregnant women and share the same culture and language, which allows for mediation with the health systems and adherence of pregnant women to prenatal care. This study aimed to describe the contributions and difficulties in the prenatal care of Guarani and Kaiowá indigenous women by Indigenous Health Agents. This is a descriptive-exploratory research with a qualitative approach, based on primary data, carried out with 33 AIS who lived and worked in four villages in the State of Mato Grosso do Sul, Brazil, from May to July 2018. The data collection technique was the focus group, through an instrument with guiding questions, with recording and full transcription of the AIS speeches, and subsequent readings to deepen Bardin's content analysis. The following categories were highlighted: “contributions of AISs in prenatal care to women's health” and “difficulties presented by AISs in prenatal care”. The experience of the AISs in the same territory as the Guarani and Kaiowá represented a contribution to the expansion and ease of access for pregnant women to prenatal care. The knowledge in biomedicine added to the knowledge of traditional practices of the Guarani and Kaiowá and good communication between the AIS and the pregnant women proved to be important for raising awareness among indigenous women regarding adherence to prenatal care. The work of the male AIS showed to be different from the female AIS regarding the approach and discovery of the pregnant woman in the territory. AISs can be important EMSI facilitators for pregnant women's adherence to prenatal care through reciprocity networks. The results indicated some social factors that intervene in the dialogue and monitoring of women's prenatal care, related to gender issues, gossip networks and images about motherhood. These factors influence access to indigenous women and the approach to themes related to pregnancy and childbirth.